Developmental care pathway for hospitalised infants with CHD: on behalf of the Cardiac Newborn Neuroprotective Network, a Special Interest Group of the Cardiac Neurodevelopmental Outcome Collaborative - Lisanti, Amy J.; Vittner, Dorothy J.; Peterson, Jennifer; Van Bergen, Andrew H.; Miller, Thomas A.; Gordon, Erin E.; Negrin, Karli A.; Desai, Hema; Willette, Suzie; Jones, Melissa B.; Caprarola, Sherrill D.; Jones, Anna J.; et al. (Cardiology in the young, 2023)
Infants and children born with CHD are at significant risk for neurodevelopmental delays and abnormalities. Individualised developmental care is widely recognised as best practice to support early neurodevelopment for medically fragile infants born premature or requiring surgical intervention after birth. However, wide variability in clinical practice is consistently demonstrated in units caring for infants with CHD. The Cardiac Newborn Neuroprotective Network, a Special Interest Group of the Cardiac Neurodevelopmental Outcome Collaborative, formed a working group of experts to create an evidence-based developmental care pathway to guide clinical practice in hospital settings caring for infants with CHD. The clinical pathway, “Developmental Care Pathway for Hospitalized Infants with Congenital Heart Disease,” includes recommendations for standardised developmental assessment, parent mental health screening, and the implementation of a daily developmental care bundle, which incorporates individualised assessments and interventions tailored to meet the needs of this unique infant population and their families. Hospitals caring for infants with CHD are encouraged to adopt this developmental care pathway and track metrics and outcomes using a quality improvement framework.